Mapping of Food Supply Ecosystem Services in Malang Regency - Arysandi, Safira Arum; Santosa, Langgeng Wahyu; Sudrajat (Journal of Geosciences and Environmental Studies, 2025)
The increase in population is in line with the increase in resource use, including the need for land as a space for human activities to meet their needs. Land conversion, primarily agricultural land, into non-agricultural land can reduce the ability of land ecosystems to provide food. This research aims to assess the performance of ecosystem services for providing rice food in Malang Regency. The study used the Simple Additive Weighting (SAW) method, a simple weighting and scoring method of land use parameters, landform ecoregions, natural vegetation types, soil types, and rainfall to determine ecosystem services for food provision. The results showed that the Malang Regency area consists of 5 classes of Ecosystem Service Performance Index (ESPI) for rice food providers, including Very High, High, Medium, Low, and Very Low. The Medium class is the ESPI class with the highest area of 117,452.85 hectares or 34% of the total area. Followed by Low ESPI class 99,980.31 hectares (29%), High ESPI class 90,742.14 hectares (26%), Very Low ESPI class 19,191.28 hectares (6%), and Very High ESPI class 17,442.59 (5%).